Fresh winds for Biskopsgården; the need for public spaces in developing neighbourhoods - Antoniazzi, Taavi (My University, 2024)
Gang violence and criminal activities are significant issues in Sweden, particularly in areas designated as ‘vulnerable’, where parallel social structures and a high concentration of crime accure. This spiral of violence has a direct impact on residents of ”vulnerable areas”. Unfortunately, the solutions proposed by politicians and officials for tackling violence and criminality are often short-term and lack a vision of the future and fail to consider a human aspect of the situation (Bergvall, 2023). Moreover, discussions frequently forget the importance of social cohesion among inhabitants in the so-called “vulnerable areas”. This thesis focuses on Biskopsgården, a district in Sweden’s second-largest city Gothenburg, classified as a vulnerable by the police, and explores potential solutions to its problems related to crime and segregation. Examining if these problems are caused by or related to the district’s layout can help to identify longterm and potentially architectural solutions to urgent problems. In order to learn from the past and to avoid controversial demolition tactics of whole neighbourhoods like in Denmark, this Master thesis will look at the historical planning of Biskopsgården and other districts from the same time that were planned with similar ideals. This historical analysis of the functionalist planning during the mid-nineteenth century lays the foundation of future design decisions and will bring valuable information that could avoid demolition and will ultimately lead to design decisions that respect the current residents. The City of Gothenburg has already proposed plans to redevelop Biskopsgården through urban densification, particularly in the central area of Friskväderstorget. In this thesis, I will critically study the plans with an historical analysis in mind and will present an alternative proposal. This thesis argues that the plans from the City of Gothenburg are, apart from the general right intentions of bringing long term change to the district, insufficient to counteract segregation and are at the same time even threatening the existing social cohesion in Biskopsgården. The alternative design of Friskväderstorget will prioritise social architecture, focusing on the social coherence of current residents. The development of public spaces is a key aspect of the design. Further, the design also considers the future needs of the Biskopsgården community.
Keywords: Urban meeting spaces, functionalism, vulnerable area, Friskväderstorget, Biskopsgården